the Influence of Emotional Intelligence on Performance State Civil Apparatus in the Pamong Praja Police Unit West Sumbawa District - Syamsu, Badrus; Umar, Umar; Khadafie, Muammar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The aim of this research is to determine the implementation and influence of emotional intelligence on the performance of State Civil Apparatus in the West Sumbawa Regency Civil Service Police Unit. The research method used is the research method Mix method. The population of this study was all ASNs in the West Sumbawa Regency Civil Service Police Unit, totaling 197 people. The sample for this research was 131 people taken using the Jalaludin Rahmat formula with a random proportional random sampling technique. The data collection technique for the ASN emotional intelligence variable used a questionnaire technique. The data analysis techniques used are correlation, regression and determination tests. Based on the results of research data analysis, it can be concluded that: 1) There is a close relationship between emotional intelligence and the performance of Civil Servants within the West Sumbawa Regency Civil Service Police Unit, 2) Based on the regression equation, it can be explained that if ASN has good emotional intelligence, then ASN performance will also increase. 3) Based on the calculation of the Coefficient of Determination (KD) to determine the magnitude of the contribution made by the emotional intelligence variable to the performance variable, it is 69.44%, meaning that the emotional intelligence variable contributes 69.44% to changes in the ASN performance variable. Meanwhile, the other 30.56% also contribute performance comes from other factors, in this case not included in the study.